A Developmental Study on Enhancing Secondary School Students’ Chinese Listening and Speaking Skills through Virtual Scenario-Based Learning Skills - Tocharoenbodee1, Chanyapak; Yinsheng, Li (Journal of Dhamma for Life, 2025)
This research aimed to: (1) develop a virtual scenario-based learning management model to enhance Chinese listening and conversational speaking skills in daily life among secondary school students, (2) compare students’ Chinese listening and speaking skills before and after learning through the virtual scenario-based learning model, (3) compare the Chinese listening and speaking skills of students taught through the virtual scenario-based learning model with those taught through conventional instruction, and (4) present an effective virtual scenario-based learning management model for Chinese language learning. This study employed a quasi-experimental research design. The sample consisted of 68 Grade 9 students from a secondary school under the Ministry of Higher Education, Science, Research and Innovation in Bangkok during the 2024 academic year. The participants were selected using simple random sampling and divided into an experimental group (n = 34), which received instruction through virtual scenario-based learning, and a control group (n = 34), which received conventional instruction. The research instruments included (1) eight lesson plans based on virtual scenario-based learning with an index of item-objective congruence of 0.96, and (2) a Chinese listening and speaking skills test. Listening skills were assessed in terms of main idea comprehension, vocabulary and sequence understanding, conversational response, and narrative retelling. Speaking skills were evaluated based on fluency, grammatical accuracy and vocabulary use, communicative effectiveness, and pronunciation, including intonation and non-verbal expression. Data were analyzed using mean, standard deviation, and t-test. The research findings revealed that (1) the post-test mean scores of Chinese listening and speaking skills of the experimental group were significantly higher than the pre-test scores at the .05 level, and (2) the post-test mean scores of the experimental group were significantly higher than those of the control group at the .05 level. The results indicate that the virtual scenario-based learning management model effectively enhances students’ Chinese listening and conversational speaking skills in daily life and is more effective than conventional teaching methods.